The comprehensive study on hydrocarbon fuel pyrolysis and heat transfer characteristics. (5th May 2017) - Liang, Ce; Wang, Yu; Jiang, Shuchao; Zhang, Qiyi; Li, Xiangyuan
Highlights: The pyrolysis and the heat transfer characteristics of n -decane were investigated. ANN has successfully explored to predict the local properties of the fluid. Heat transfer coefficients were influenced by both pyrolysis and heat flux. Heat transfer performed great advantages at low pressure and high heat flux. Abstract: The heat transfer characteristics of endothermal hydrocarbon fuel are very critical for regenerative cooling engines in high speed flight. The objective of this paper is to investigate the influence of high pyrolysis on heat transfer performance, and also including the impact of pressure and heat flux on heat transfer. A series of experiments under different conditions were carried out using n -decane. The investigation is based on three pressures of 1 MPa, 2.5 MPa and 4 MPa respectively, using resistance heating tube to simulate conditions encountered in regenerative cooling engines with a length range of 30–100 cm. The bulk inlet and outlet temperatures of fuel were held constant at 480 °C and 530–780 °C respectively in test section. On the basis of the experimental data, artificial neural network (ANN) had been successfully explored to predict the local properties of the fluid, which are very important in heat transfer. Furthermore, the heat transfer coefficients were found to be influenced by both pressure and heat flux, and there exists a critical heat flux at about 0.4–0.5 MW/m 2 for sub-and super-critical pressure. Relatively low pressure of pyrolysis had great advantages under the condition of relatively high heat flux because of the higher heat transfer coefficients and less coking.